Mandeh Special Economic Area (Kek) as The Model of Sharia Tourism Development in West Sumatra Province - Ansharullah Ansharullah; Harum Natasha (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study is entitled "Models For Mandeh Special Economic Areas As The Development Of Sharia Tourism In West Sumatra Province". The research objective is to determine the model of the implementation of the Mandeh Special Economic Zone (KEK) as sharia tourism in West Sumatra Province in fulfilling the sharia tourism requirements. Data collection methods used were questionnaires and documentation. Data processing using quantitative descriptive techniques with percentages. Based on the results of the study it can be concluded that the Recapitulation of Tourist Perceptions of the application of the Mandeh Special Economic Zone (SEZ) model as a shariah-compliant destination is categorized as very good.